A Ship Grounding Over a Century Ago Left a Lasting Channel Among Corals - Thomas M. DeCarlo; Leticia Cavole; Gabriel Castro‐Falcón; Vinícius Ribau Mendes; Guilherme Ortigara Longo; Natan S. Pereira; Cristiano Mazur Chiessi (Ecology and Evolution)
ABSTRACT Among disturbance events to coral reef ecosystems, ship groundings can be among the most acute due to the physical damage they cause to coral reef habitats. Following ship groundings, monitoring studies show that some reefs recover whereas others retain changes in coral community structure for at least a decade. Thus, the recovery timescales following groundings are variable, but the general paradigm is that reef communities will begin on a trajectory toward recovery to the pre‐disturbance state. Here, we report several lines of evidence of a 100+ year old ship grounding in northeastern Brazil. Strikingly, the ship grounding led to a semi‐permanent sand channel in the reef that has not substantially trended toward recovery. Our observations support the notion that acute disturbance on coral reefs can cause structural changes that may never return to the pre‐disturbance conditions.